Flash flood simulations for an Egyptian city - mitigation measures and impact of infiltration. Issue 5 (27th May 2020) - Tügel, Franziska; Özgen-Xian, Ilhan; Marafini, Ester; Hadidi, Ahmed; Hinkelmann, Reinhard
ABSTRACT: Within this work, the impact of mitigation measures and infiltration on flash floods is investigated by using a 2D robust shallow water model including infiltration with the Green-Ampt model. The results show the combined effects of infiltration and mitigation measures as well as the effectiveness of bypass channels in addition to retention basins. Retention basins at appropriate locations could reduce the maximum water depth at critical locations by 23%, while the additional implementation of drainage channels lead to a reduction of 75%, considering also infiltration lead to a further reduction of 97%. If infiltration was considered without mitigation measures, the peak water depth was reduced by 67%. For an exceptional extreme event the measures lead to a reduction of 73% at some locations, while at other locations the overflow from retention basins due to overstraining generated even higher inundations with an increase of 58%.